3(x-4)+4x-7=-3x+11

Simple and best practice solution for 3(x-4)+4x-7=-3x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-4)+4x-7=-3x+11 equation:


Simplifying
3(x + -4) + 4x + -7 = -3x + 11

Reorder the terms:
3(-4 + x) + 4x + -7 = -3x + 11
(-4 * 3 + x * 3) + 4x + -7 = -3x + 11
(-12 + 3x) + 4x + -7 = -3x + 11

Reorder the terms:
-12 + -7 + 3x + 4x = -3x + 11

Combine like terms: -12 + -7 = -19
-19 + 3x + 4x = -3x + 11

Combine like terms: 3x + 4x = 7x
-19 + 7x = -3x + 11

Reorder the terms:
-19 + 7x = 11 + -3x

Solving
-19 + 7x = 11 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-19 + 7x + 3x = 11 + -3x + 3x

Combine like terms: 7x + 3x = 10x
-19 + 10x = 11 + -3x + 3x

Combine like terms: -3x + 3x = 0
-19 + 10x = 11 + 0
-19 + 10x = 11

Add '19' to each side of the equation.
-19 + 19 + 10x = 11 + 19

Combine like terms: -19 + 19 = 0
0 + 10x = 11 + 19
10x = 11 + 19

Combine like terms: 11 + 19 = 30
10x = 30

Divide each side by '10'.
x = 3

Simplifying
x = 3

See similar equations:

| 2(10)-y=14 | | 5.5+2x=41.5 | | 19.9x+10=34+9.9x | | 3x^2+12=20x | | p=60-3q | | x=5-3y | | Y+(y+1)+(y+2)=45 | | (3t-12)=27 | | a^3-8a=3 | | 6=10-4 | | 36=7b+1 | | 5x-7=(-6)x-29 | | 4x-2(x-5)=-3+4x+4 | | -p-2=18-27p+6 | | 1650+x(145.50)=3250.50 | | 22c+17=11+3c | | 10=0.3x+9.1 | | -9x-7(0)=-30 | | 2x^4-4x^3-1x^2=0 | | 6=-5x+21 | | 36+3y=3y-24 | | 3t-t-8=t-8 | | 10=0.3k+9.1 | | 3=-14-4 | | x^3-3-5x+3=-3x^2+10 | | Log(-9-5x)=1 | | 4x+8-3x+7=x+7 | | 2.5p-4(p+7)=0 | | 4x-5(x+6)=1 | | 12x+9y=564 | | 6(4a-5)=-30-8a | | 53a+21=a |

Equations solver categories